Analyzing the use of social networks sites in the purchasing decision process - Miranda, F. J.; Rubio, S.; Chamorro, A.; Loureiro, S. M. C. (Encyclopedia of e-commerce development, implementation, and management, 2016)
Social networks have quickly become a platform in which citizens feel comfortable interacting with each other. They have not only become a sociological phenomenon, but also a marketing opportunity that firms are unwilling to let go by. This is a new ecosystem in which individuals are as important as firms or the media – an environment in which people are what is important, and one which is having an increasing influence in the business world.